PENGGUNAAN METODE BLENDED LEARNING DENGAN MEDIA YOUTUBE BAGI MOTIVASI BELAJAR MAHASISWA DI MASA PANDEMI - Sandha Soemantri; Rio Febrianto Arifendi (Inteligensi : Jurnal Ilmu Pendidikan, 2022)
This study aims to describe the results of student learning motivation after attending lectures using the blended learning method with YouTube media during a COVID-19c in the mathematics education department, Universitas Muhammadiyah Surabaya. This research was conducted because during the Covid COVID-19c there was a change in the flow of education which resulted in a decrease in motivation to study due to signal constraints, the ability to provide internet quota, and limited access. The type of research used in this study is a qualitative method with the subject of all students taking multivariable calculus courses as many as 35 students. The data collection technique uses a learning motivation questionnaire and is confirmed through interviews. The results showed that the blended learning method with YouTube media was able to increase student learning motivation and help students understand the material well, because students who felt left behind could repeat material videos and discuss together to complete the exercises and assignments given.